VALUE OF AMINOTRANSFERASES IN LIVER CIRRHOSIS - Miroslava Mihaylova; Strahil Strashilov; Pencho Tonchev (Peytchinski Publishing, 2024)
Aim: To ditermine values of ASAT and ALAT and their ratio in different stages of liver cirrhosis. Material and methods: A retrospective study was conducted, including patients with newly diagnosed liver cirrhosis from 01.01. 2017 to 31.12. 2021. Of all, 258 (71%) were men and 103 (29%) were women. The mean age of the study population was 57±11.4 years, with alcohol as the leading etiology in 262 (72.6%) of all cases. AT were measured at an upper reference limit of 40UI/ml. All were staged by Child-Pough and MELD Na score. IBM SPSS 26 and Excel statistics for data processing were used at a significant level of p< 0.05. Results: Of all 361 individuals, normal AT were measured at 89 (24.7%), at 96 (25.76%) only with normal ASAT and at 233 (66.77%) only with normal ALAT. The mean value of ASAT increases significantly depending on the Child stage (p=.004) and is close to the significance of MELD Na (p=.036). Mean ALAT values were minimal to moderately elevated, with no significant association with them (p=.647, p=.020). 90% of individuals had an ASAT/ALAT ratio above 1, which showed substantial dependence on Child and MELD Na (p=.000, p=.000). A ratio above 2 was found at 194 (53.7%) mainly in Child C, which was associated with alcohol etiology. Conclusion: The absolute values of ASAT and ALAT have no relationship with the severity of liver cirrhosis, unlike their ratio, which significantly increases.